Arm swing during skating at different skiing speeds affects skiing mechanics and performance - Göpfert, C.; Lindinger, S. J.; Ohtonen, O.; Rapp, W.; Müller, E.; Linnamo, V. (Translational Sports Medicine, 2018)
Arm swing has been shown to lead to greater maximal speed and movement economy in cross-country skiing. The current study aimed to investigate how arm swing alters skiing mechanics and contributes to performance and acceleration of the athlete's centre of mass (COM). While skiing on snow, seven highly skilled cross-country skiers simulated V2-alternate skating without using ski poles and with double or single arm swing and without arm swing. During leg push-off the linear momentum of the body increased due to arm swing. Simultaneously, linear momentum of the arm(s) decreased in arm swing trials, indicating a transfer of momentum from arms to the rest of the body and being more prevalent with double arm swing compared to single arm swing (all P < 0.05). Greater maximal skiing speeds were reached with single and double arm swing, while the forward lean angle, the force leading to acceleration of COM in skiing direction, and the force effectiveness increased (all P < 0.05). The effects of less mass moving in single arm swing could be compensated by carrying out the arm swing faster, almost aligned in skiing direction and with a "long arm" pattern, indicating how arm swing can be conducted efficiently.